Managing Organizational Climate for Improved Employees’ Performance in Selected Manufacturing Companies in Asaba, Delta State, Nigeria - Dumebi Anthony Ideh; Akeem Ayofe Akinwale; Samuel Chidiebere Okeke (Petra International Journal of Business Studies, 2024)
Achieving sustainable employee performance improvement has remained a significant challenge in many contemporary organizations despite recognizing the implications of improved employee performance for organizational effectiveness.  Therefore, this study examined how organizational climate can be managed to enhance employees' performance, focusing on how each of the four dimensions of organizational climate (rewards management, management styles, organizational policies, and training and development) affect employees’ performance. A survey research design was used in the study. The study population comprised 593 employees, from whom 238 were purposively selected as respondents, and 238 copies of a structured questionnaire were administered to the participants. Of the number of copies administered of the questionnaire, 202 were returned and used for data analysis as they were correctly filled out. The collected data were analyzed using descriptive and inferential statistics: frequency distribution and regression. The hypotheses were tested with multiple regression, and the findings revealed that rewards management and management styles significantly influenced employees’ performance. The study concluded that effective management of organizational climates, such as rewards management and management styles, improved employee performance. Thus, manufacturing companies should pay adequate attention to organizational climate to encourage improved employee performance.